Extractive Waste Management in Coal Surface Mining Projects—A Circular Economy Approach - Ariadni Sokratidou; Christos Roumpos; Nikolaos Paraskevis; Aikaterini Servou; Francis Pavloudakis (Materials Proceedings)
Coal surface mines usually occupy large areas for the development of mining activities, and they affect and change the landscape and land cover in various ways. After completing the exploitation of a specific mine section, the sustainable reclamation of mining land is directly associated with the optimal exploitation of waste dumping sites. This study investigates the main issues related to extractive waste management concerning the progressive development of dumping sites in continuous surface mining projects, from initial excavations to the completion of mining operations and post-mining utilization, considering basic geospatial parameters and circular economy principles. In this framework, the waste dumping areas of the exhausted Amyntaion lignite mines in North Greece are examined. Research results showed that the waste management that was applied in this area was characterized by sustainable attributes, and an equilibrium was observed in the dumping material volume.